Intraperitoneal vancomycin treatment of multifocal methicillin-resistant Staphylococcus aureus osteomyelitis in a patient on peritoneal dialysis. (11th September 2020) - Abid, Qassim; Asmar, Basim; Kim, Edward; Molloy, Leah; Gregory, Melissa; Valentini, Rudolph P
Abstract: Purpose: We report the case of a 2-year-old girl with end-stage renal disease managed by peritoneal dialysis (PD) who developed methicillin-resistant staphylococcal osteomyelitis of the left shoulder and was successfully treated with intraperitoneal (IP) administration of vancomycin for 2 weeks followed by oral clindamycin therapy. Summary: The patient was hospitalized with tactile fever and a 3-day history of worsening fussiness. Radiography of the left shoulder showed findings indicative of osteomyelitis. Vancomycin was administered via central venous line for 3 days, during which time the patient underwent PD 24 hours a day. After magnetic resonance imaging revealed proximal humeral osteomyelitis, septic arthritis of the shoulder joint, and osteomyelitis of the scapula, the patient underwent incision and drainage of the left shoulder joint. Both blood and joint drainage cultures grew methicillin-resistant Staphylococcus aureus that was sensitive to vancomycin. The patient's central venous catheter was removed on hospital day 4; due to difficulties with peripheral i.v. access and a desire to avoid placing a peripherally inserted central venous catheter, vancomycin administration was changed to the IP route, with vancomycin added to the PD fluid. During IP treatment, serum vancomycin levels were maintained at 13.5 to 18.5 mg/L, and the calculated ratio of vancomycin area under the curve to minimum inhibitory concentration was maintained above 400. After completing a 14-day course of IP vancomycin therapy, the patient was switched to oral clindamycin, with subsequent complete resolution of osteomyelitis. Conclusion: IP vancomycin was effective for treatment of invasive S. aureus infection in this case. This approach should be considered in patients undergoing PD for whom peripheral i.v. access options are limited and/or not preferred.